2000
DOI: 10.1021/jo005534x
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Ring-Closing Metathesis in the Synthesis of Dihydropyrans

Abstract: An investigation into the factors influencing the diastereochemical outcome of the ring-closing metathesis based synthesis of dihydropyrans is presented in this paper. Divinyl carbinols derived from alpha-hydroxy carboxylic acid esters are elaborated to trienes with two diastereotopic vinyl moieties. Depending on the steric demand of the oxo substituent of the divinyl carbinol moiety (either unprotected OH, TBDMS, or benzyl ether) different diastereomers are preferrably formed upon ring-closing metathesis. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 36 publications
(34 reference statements)
0
41
0
1
Order By: Relevance
“…Recently, it has been shown that an indenylidene-ruthenium catalyst was able to perform ring closing metathesis (RCM), isomerisation and Claisen rearrangement, successively. [8] By contrast, in the study of in situ prepared imidazolinylidene-ruthenium catalysts for RCM of 1,6-dienes and 1,6-enynes [12 -14] we found initial results [15] showing that these catalysts did not perform RCM or cycloisomerisation of 1,7-dienyl ethers but selectively led to tandem isomerisation/ Claisen rearrangement affording g,d-unsaturated aldehydes (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that an indenylidene-ruthenium catalyst was able to perform ring closing metathesis (RCM), isomerisation and Claisen rearrangement, successively. [8] By contrast, in the study of in situ prepared imidazolinylidene-ruthenium catalysts for RCM of 1,6-dienes and 1,6-enynes [12 -14] we found initial results [15] showing that these catalysts did not perform RCM or cycloisomerisation of 1,7-dienyl ethers but selectively led to tandem isomerisation/ Claisen rearrangement affording g,d-unsaturated aldehydes (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Optical purities were determined by HPLC using a HP-LC-1050 system equipped with a Daicel Chiralcel OD column. The following compounds were prepared according to procedures described in the literature: 10c, [45] 10d, [47] 10e, [46] 10g, [49] 10h, [56] 10i, [3] 10j, [57] Pd 2 (dba) 3 · CHCl 3 , [58] [Pd(h 3 -C 3 H 5 )Cl] 2 , [59] and [Pd(PPh 3 ) 4 ]. [58] Screening Experiments for Different Pd-Precatalysts…”
Section: Resultsmentioning
confidence: 99%
“…Spectroscopic data are identical to those reported in the literature. [3] Optical rotation compares well to the val- …”
Section: General Procedures For the Pd-catalyzed Allylationmentioning
confidence: 90%
See 2 more Smart Citations